PWE-167 Effect Of Linaclotide On Ibs-qol Sexual Subscale Scores In Patients With Irritable Bowel Syndrome With Constipation: Results From 2 Phase 3 Trials. (9th June 2014) - Currie, M; Shiff, S; Hao, X; Carson, R; Baird, M; Johnston, J
Abstract : Introduction: Linaclotide is a minimally absorbed guanylate cyclase-C agonist approved for treatment of IBS with constipation (IBS-C). IBS often results in diminished quality of life (QOL), including decreased sexual desire and activity. This post-hoc analysis aimed to determine if linaclotide treatment improved IBS-QOL sexual subscale scores in IBS-C patients, compared to placebo. Methods: Data from 2 randomised, double-blind Phase 3 linaclotide trials in IBS-C were pooled. The IBS-QOL was administered at baseline and Week 12. The sexual subscale includes items on difficulty with sexual activity and reduced sexual desire, both rated on a 5-point scale (1=not at all, 2=slightly, 3=moderately, 4=quite a bit, 5=extremely/a great deal); the sum of both items is scaled to 0 (worst) to 100 (best). Changes in the scores from baseline to Week 12 were compared for linaclotide- vs placebo-treated patients in the intent-to-treat (ITT) population and the Impaired Sexuality (IS) subgroup (baseline sexual subscale scores ≤50). Results: Of 1598 ITT patients with baseline sexual subscale scores, 522 (33%) had a score ≤50 indicating significant impact of IBS on sexual desire and activity (females: 484/1439 [34%]; males: 38/159 [24%]). At Week 12, linaclotide significantly improved change-from-baseline sexual subscale scores vs placebo in the ITT population and IS subgroup (Table, p < 0.001 for both). Although baseline scores for males were higher (better) than for females, improvement vs placebo for males was similar to females in the ITT population and greater for the IS subgroup. However, the male sample size was too small to establish statistical significance. Conclusion: Linaclotide treatment significantly improves IBS-QOL sexual subscale scores in IBS-C patients compared with placebo, in both the total population and in patients with impaired sexuality at baseline. Study funded by Forest Laboratories, Inc., and Ironwood Pharmaceuticals, Inc. Disclosure of Interest: M. Currie Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, S. Shiff Shareholder of: Forest Research Institute, Employee of: Forest Research Institute, X. Hao Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, R. Carson Shareholder of: Forest Research Institute, Employee of: Forest Research Institute, M. Baird Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals, J. Johnston Shareholder of: Ironwood Pharmaceuticals, Employee of: Ironwood Pharmaceuticals.